Optimum thresher parameters for high moist paddy - HAMZA MOLLAKADAVATH; Dr. M Sivaswami (Guide) (Tavanur 1993 Kelappaji College of Agricultural Engineering and Technology)
Optimum thresher parameters for high moist paddy
Optimum thresher parameters for high moist paddy